Thermal fluid-structure interaction analysis on flexible printed circuit board during reflow soldering. - Muhammad Iqbal Ahmad (2021)
The flexible printed circuit boards (FPCB) offer several advantages in meeting the electronic applications' growing demands. Certain limitations like inadequate reflow profile cause reliability issues in the manufacturing assembly process. The study aims to investigate the characteristics of infrared (IR) reflow oven characteristics to determine the suitable operating conditions for the FPCB soldering process. The reflow's experimental work was used as a benchmark for developing the numerical model, and the reflow profile was described based on the standards of JSTD-020E. The numerical model was developed using thermal fluid structure interaction (FSI) concepts based on actual dimensions and appropriate boundary conditions. The model was validated with the experimental data to determine how much the realistic model can effectively imitate the observed behavior. Further studies were carried out using the developed model to analyze the correlation of several parameters with reflow performance and FPCB with the ball grid array package. From the findings, the simulation of the model showed acceptable consensus with the experimental at average error of (< 5% ) for fluid and (<15 %) for structural domain, respectively. It was found that the temperature distribution was inhomogeneous along with the reflow phases (140, 180 , 205 C). An in-depth study using the simulation approach revealed that the desktop reflow oven's temperature distribution was dependent on several factors, namely fan speed (Re, 0.43×105 ~ 2.65×105), PCB position, PCB thickness (25- 125 m), and cooling period (62-302 s). The rotational fan had resulted in an unsteady flow that induced inhomogeneous temperature at different positions in the reflow oven cavity. This study's findings highlight that the thin FPCB had exhibited different surface temperature profiles, which subsequently reflected on the heat flux generated (94 W/m2) from the infrared heater. A cooling period of 122 s was suggested for improved heating attributes. However, increasing the FPCB thickness led to a lower temperature, deformation and von Mises stress distribution, whereas Ag content's addition led to contrasting results. After the reflow oven evaluation, a reliability study was conducted, and it was found that the fracture mode on the FPCB occurred between the interface of the copper pad and solder joints. Concerning different Ag contents, a slight improvement in the shear strength (up to 27.8 MPa) was revealed upon the increase in Ag content in the solder joints. Overall, the initiate approached significantly reduced the solder joint defects and enhanced solutions to producing lead-free solders with reduced reliability issues in the electronics manufacturing industry.